2008
DOI: 10.1007/s10620-008-0278-y
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Muscle Function in the Human Esophagus with Age

Abstract: Most studies on the effect of aging on esophageal motor function have shown that peristaltic function deteriorates with age. Esophageal motor function is traditionally studied by means of manometry and radiography. Distension of the esophagus with evaluation of active and passive mechanical parameters have become available during recent years. In this study, we did a manometric swallow analysis and used the distension method to study esophageal properties and function during aging. An impedance planimetric pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 26 publications
4
51
0
2
Order By: Relevance
“…43 Several studies showed that esophageal distensibilities are decreased and LES pressures are higher in aged subjects. 5,[44][45][46] However, basal LES pressures of the older group was not higher than that of the younger group which needs explanation regarding age definition or characteristics of the aged group. In the present study the definition of the aged group were subjects over 65 years old, which is lower than that of previously published papers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…43 Several studies showed that esophageal distensibilities are decreased and LES pressures are higher in aged subjects. 5,[44][45][46] However, basal LES pressures of the older group was not higher than that of the younger group which needs explanation regarding age definition or characteristics of the aged group. In the present study the definition of the aged group were subjects over 65 years old, which is lower than that of previously published papers.…”
Section: Discussionmentioning
confidence: 84%
“…2,3 Several studies showed decreased sphincter relaxations and decreased esophageal contraction and dilatation in the aged people. [4][5][6] The neural control of gastrointestinal function, including esophageal motility is related to enteric neurons. 7,8 It has been shown that changes in esophageal physiology is associated with loss of esophageal myenteric plexus neurons, which are part of the enteric nervous system (ENS) and lie within the smooth muscle layers of the esophageal wall in the aged population.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is drawing increasing attention due to the modern lifestyle, prevalence of obesity (4), sleep apnea (5) and metabolic syndrome (6), progression of aging and decline of Helicobacter pylori infection in developed countries (7). Lower esophageal sphincter relaxation is frequently observed in obese populations (4) and those with a full stomach (8) or sleep apnea (5), whereas hiatal hernias are prevalent in the elderly (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although AF and GERD share the same predisposing factors, including metabolic syndrome (3,6), sleep apnea (2,5) and senescence (1,9), their association remains controversial. We conducted a preliminary questionnaire study and reported that the coexistence of AF and GERD is not unusual in Japan (10).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, deleterious effects of aging on the structure and function of many organs are well recognised [9,16,17,19,27]. Oesophageal dysfunctions related to aging are clinically well described [4,8,10,14,23], but histological reports are not numerous and mostly focus on the swallowing reflex structures and the oesophageal sphincter [3,12,20,30]. Interestingly enough, histomorphometric examinations focused on the other parts of the human oesophagus are absent.…”
Section: Introductionmentioning
confidence: 99%